Big Bluestem and Indiangrass from Remnant Prairies: Plant Biomass and Adaptation. Issue 2 (1st March 2018) - Vogel, Kenneth P.; Johnson, K. D.; Carlson, I. T.; Schmer, Marty R.
Abstract : Big bluestem ( Andropogon gerardii Vitman) and indiangrass ( Sorghastrum nutans L.) were collected from remnant Midwestern prairies and evaluated as individual prairie accessions in replicated space‐transplanted nurseries near Mead, NE, Ames, IA, and West Lafayette, IN. The objective was to determine the extent of differences among the accessions for plant biomass (g plant −1 ) and biomass quality, the extent of strain × location interactions, and the relationship between geographical locations of collection sites and evaluation locations for plant biomass production. Plant biomass has been used previously as a measure of plant adaptation and fitness. Big bluestem and indiangrass accessions differed significantly ( P < 0.05) for plant biomass at all locations. Strain mean squares for plant biomass were 10× greater than strain × location effects for big bluestem and were not significant for indiangrass, indicating a general lack of specific adaptation across the Midwest. Accessions were identified that had high plant biomass at all three locations. These accessions should have value in breeding programs and for use in revegetation. Regression analyses were used to test the effect of north‐to‐south, east‐to‐west, and direct distances between the collection sites and the evaluation locations on plant biomass. The most important distance effects were the north‐to‐south effects, which were significant for plant biomass for big bluestem at all locations and for indiangrass at West Lafayette. Moving northern big bluestem accessions south resulted in reduced plant biomass, with the opposite effect when southern accessions were moved north. Results support the regional adaptation of the best accessions and cultivars for these grasses.